Effects of different doses of skt-b vibrio probiotic bacteria addition on survival and growth rate of tiger shrimp (Penaeus monodon) larva - . Widanarni; M.A. Lidaenni; Dinamella Wahjuningrum (Jurnal Akuakultur Indonesia)
Probiotic bacteria has been widely used as biocontrol agents in tiger shrimp hatcheries.  Vibrio SKT-b is one of the probiotic bacteria candidates that could suppressed the growth of pathogenic bacteria Vibrio harveyi and could increase survival rate of tiger shrimp larva. This experiment was carried out to study the effects of probiotic bacteria SKT-b Vibrio addition at different doses on survival and growth rate of tiger shrimp larva.  Experiment was conducted with five treatments and three replications, consisted of SKT-b Vibrio probiotic bacteria addition at the doses of 103 CFU/ml, 104 CFU/ml, 105 CFU/ml, and 106 CFU/ml and control (0 CFU/ml).  Results showed that optimum dose of probiotic bacteria for tiger shrimp was 104 CFU/ml with a survival rate of 94.67%. However, the addition of probiotic bacteria at this particular dose did not significantly increase shrimp growth rate as compared with control.